Going back to our future : carrying forward the spirit of pioneers of science education - Pedersen, Jon E.; Finson, Kevin D.; Spector, Barbara S.; Jablon, Paul (Pioneers of science education., 2013)
This book is the first volume of an attempt to capture and record some of the answers to these questions--either from the pioneers themselves or from those persons who worked most closely with them. We know there are many pioneers and early trailblazers who are not included in this volume, but there are other volumes to follow. As we have posed questions, rummaged through files and oft-neglected books, and probed the memories of many individuals, we have come to realize our list of true pioneers is ever growing. There are names on the list that most of us readily recognize, and there are names of whom few of us have heard--yet who were significant in their roles as mentors or idea development and teaching. We quickly discovered that the "family tree" showing connections between these people is not a neat, clean simple branching tree, but is more like spaghetti. The connections are many, are intertwined, and all have their significance. The stories in this volume demonstrate how vital this network was in supporting the individual pioneers during their journey in difficult times and continues to be for those of us today in our own enterprise.